Spinozist Apiculture: Labor and the Problem of Interspecies Recognition in the Short Treatise - Nicolas Lema Habash (Journal of Spinoza Studies)
This article inscribes itself in a double domain within Spinoza studies: understanding the status of animals in his philosophy and exploring an idea of work in his writings. Its main focus is a specific passage in the Short Treatise, where Spinoza describes the bees as working towards their own ends and as instruments from whom human beings can obtain advantages. The study of this passage on the relationship between the bees and the human being will sketch out some elements for a theory of labor in Spinoza. I show that what I call Spinoza’s “apicultural labor complex” provides a theory of work wherein labor institutions may be established through relationships of what I term “care.” Key here is Spinoza’s notion of werktuig (instrument): it conceptualizes a relationship of mutual well-being, even if one individual is more powerful than another in a specific transindividual complex. These caring relationships imply a form of recognition qua practical knowledge towards another singular life form and, more specifically, about how to aid other individual existences to thrive through the achievement of joy (gaudium). In addition, I will establish that one way of conceptualizing resistance to labor in Spinoza’s philosophy is through a notion of recognition, considered as a principle of conflict and dis-identification of the (human or more-than-human) individual’s position in the social field.